Sentidos-e-significados atribuídos ao gênero oral seminário: uma investigação crítica - Fernandes, Elizabete Cristina de Brito (2014)
This research theme is the teaching of oral discourse genres seminar with the objective of investigating the senses-and-meanings attributed by participants - teacher and teacher researcher - about the teaching and learning of discourse seminar to understand how these senses-and-meanings are shared and critically transformed. This study was conducted within the perpective of Critical Applied Linguistics, based on Moita Lopes (2006); Signorini (2006); Fabricio (2006) and Rojo (2006). Relies on the socio-cultural-historical theory (Vygotsky, 1984/2010, 1987/2013 and their collaborators) and the concepts of speech genres (Bakhtin and the Circle 2003, among others), teaching oral speech genres (Marcuschi, 2008, among others), seminar gender and didactic sequences (Dolz Schneuwly 2004, among others). The research methodology that was used is the Criticial Interpretive methodology (Moita Lopes, 1994; 1996, among others) and the corpus is composed of two meetings between researcher and participant teacher for initial planning of activities, lectures and conversations about the classes in which there were different types of interest to the researcher, participant teacher, student and assistant professor. Both the planning of activities as the recordings of the classes were discussed during the meetings between the researcher and the participant teacher. For analysis and discussion of the results It was used the thematic content, where the analysis axes were the directions and meanings attributed by the participant-teacher and teacher researcher for the teaching of gender discourse seminar. The results obtained from the analysis of the data revealed that both initial meanings attributed by the participant teacher and the teacher researcher to the genre teaching seminar were reinterpreted, enabling the transformation of practices in the classroom as well as learning and development to the participants